2022
DOI: 10.1021/acsbiomaterials.2c01034
|View full text |Cite
|
Sign up to set email alerts
|

Oxyhemoglobin-Based Nanophotosensitizer for Specific and Synergistic Photothermal and Photodynamic Therapies against Porphyromonas gingivalis Oral Infection

Abstract: Photothermal therapy (PTT) and photodynamic therapy (PDT) are emerging alternative antibacterial approaches. However, due to the lack of selectivity of photosensitizers for pathogenic bacteria, these methods often show more or less different degrees of in vivo toxicity. Moreover, it is difficult for PDT to exert effective antibacterial effects against anaerobic infections due to the oxygen deficiency. As one of the major anaerobic pathogens in oral infections, Porphyromonas gingivalis (P. gingivalis) acquires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that P. gingivalis can bind to and acquire porphyrin molecules from Hb; therefore, Hb can be used as a specific drug delivery vehicle to treat P.gingivalis infection [252]. Based on this idea, Bai et al [253] complexed rat oxyhemoglobin (oxyHb) with an anionic amphiphilic PS (IR820) to produce a stable nano-photosensitizer oxyHb@IR820. oxyHb@IR820 targets P.gingivalis, mediating the synergistic antibacterial effects of photothermal therapy and PDT [254][255][256] and providing a new therapeutic strategy against a P.gingivalis infection.…”
Section: Nano-hbocs For Other Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that P. gingivalis can bind to and acquire porphyrin molecules from Hb; therefore, Hb can be used as a specific drug delivery vehicle to treat P.gingivalis infection [252]. Based on this idea, Bai et al [253] complexed rat oxyhemoglobin (oxyHb) with an anionic amphiphilic PS (IR820) to produce a stable nano-photosensitizer oxyHb@IR820. oxyHb@IR820 targets P.gingivalis, mediating the synergistic antibacterial effects of photothermal therapy and PDT [254][255][256] and providing a new therapeutic strategy against a P.gingivalis infection.…”
Section: Nano-hbocs For Other Biomedical Applicationsmentioning
confidence: 99%
“…Wound healing [79] ZIF-8 ZIF-8@Hb MOFs Ischemic stroke [74] Hb@AuNCs Synthesizing ultrasmall protein metal clusters Cancer [75] O 2 @Hb@ZIF-8 MOFs [72] Core-shell structural HemoAct Conjugating one Hb molecule with three HSA Ischemic stroke [140] [142] Hb-HSA 3 (PtNP) Combining platinum nanoparticles with HSA C@HPOC Protein hybridization Cancer [193] Others H-NPs Combining Hb with DAC RCC [169] V(Hb)@DOX Coupling PCL self assembles to form hollow Nanovesicles Cancer [84] HCM PMAG linking GLUT1 [82] DHCNPNPs Hb and DOX encapsulated in PLGA [83] Au-Hb@PLT Synthesized by coating Au-Hb NPs with PLT membrane [85] P-FRT-RBC Ferritin, a protein-based nanocage [76] BP@RB-Hb Assembling Hb into nanocomplexes with BP and PS [192] OxyHb@IR820 oxyHb complexed with an anionic amphiphilic PS P. gingivalis [253] MN Loading with black phosphorus Wound healing [86] G-HbOD Conjugating human Hb to the surface of gelatin microspheres 3D cell culture [257] NERBC Anchoring Hb on exogenous Ca 2+ and PO 4…”
Section: Abbreviationsmentioning
confidence: 99%
“…Among the photosensitizers examined in research involving Pg , the most extensively studied to date have been indocyanine green [ 91 , 92 , 93 ], methylene blue [ 94 , 95 , 96 ] and toluidine blue [ 97 , 98 , 99 ]. Other photosensitizers have included: aminolevulinic acid [ 100 ], azulene [ 101 ], β-NaYF 4 :Yb 3+ , Tm 3+ @TiO 2 (termed UCNPs@TiO 2 ) [ 102 ], BLC 1010 and BLC 1014 [ 103 ], cadmium telluride nanocrystals [ 104 ], captopril-protected gold clusters [ 105 ], cationic amino acid-porphyrin conjugate 4i [ 106 ], Chlorin-e6 [ 103 , 107 , 108 ], chloro-aluminum phthalocyanine [ 109 , 110 ], Coumarin 6 [ 111 ], Curcumin [ 112 , 113 ], curcumin-NP [ 114 ], cyanidin-3-glucoside [ 115 ], doxycycline [ 116 ], erythrosine [ 115 , 117 ], graphene silver polymethyl methacrylate [ 118 ], lysine-porphyrin conjugate 4i [ 119 ], meta-tetra(hydroxyphenyl)chlorin (mTHPC) [ 120 ], oxyhemoglobin-based oxyHb@IR820 [ 121 ], phenothiazine chloride [ 122 , 123 , 124 ], phloxine B [ 125 ], Photodithazine [ 126 ], phycocyanin [ 127 ], protoporphyrin IX [ 35 ], purpurin-based photosensitizer [ 128 ], Radac...…”
Section: Mode 5: Cell Lysis Through Drug/light Interaction (Apdt)mentioning
confidence: 99%
“…In this context, it is relevant to note that periodontal pathogens such as Porphyromonas gingivalis use iron for growth and thereby deplete iron and precipitate anemia. [ 10 ] Furthermore, chronic periodontitis is typically associated with elevated production of inflammatory cytokines such as IL1, IL6, and tumor necrosis factor-α. Mechanistically, these cytokines could suppress erythropoiesis, shorten RBC survival, and blunt erythropoietin response.…”
Section: Introductionmentioning
confidence: 99%